Beban Latihan, Akumulasi Beban Kerja, dan Risiko Cedera pada Pelari Jarak Jauh: Analisis Deret Waktu - Muhammad Reza Aziz Prasetya; Awang Firmansyah; Heri Wahyudi; Cheng Liang Chang; Pua Ying Zhuo (Indonesian Journal of Kinanthropology (IJOK), 2026)
Background: Monitoring training load is essential for optimizing performance while minimizing injury risk in endurance athletes. However, evidence linking daily workload fluctuations and injury occurrence in runners remains limited. Therefore, this study aimed to examine the relationship between daily training load, accumulated workload, and injury occurrence in distance runners using a longitudinal time-series dataset. Methods: A retrospective observational design was used to analyze longitudinal training data from 74 distance runners, comprising 42,766 daily observations. Training-load variables included total running distance, intensity zones, sprint distance, strength training participation, and perceived recovery indicators. Injury occurrence was recorded as a binary outcome (injury vs. no injury). Logistic regression and workload-ratio analysis were applied to evaluate associations between training load variables and injury risk. Results: The analysis identified 583 injury events across the observation period. Higher accumulated running volume and greater fluctuations in daily workload were associated with an increased likelihood of injury. In addition, reduced perceived recovery scores were linked to a higher probability of injury occurrence, suggesting the importance of internal load monitoring alongside external training metrics. Conclusions: Variations in workload progression and insufficient recovery may contribute to injury risk in distance runners. Monitoring training load accumulation and recovery indicators may help coaches and practitioners implement more effective load-management strategies to reduce injury risk while maintaining performance development.